المحاسبة عن النشاط الزراعي وإمكانية تطويرها مع دراسة تطبيقية على منشأة الحرية للإنتاج النباتي في جبلة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث المحاسبة عن النشاط الزراعي, وإمكانية تطويرها، مع دراسة تطبيقية على منشأة الحرية للإنتاج النباتي في جبلة، وذلك من خلال دراسة الواقع الراهن للمحاسبة الزراعية, وإبراز عيوبه, والعمل على تطويره بشكلٍ علمي ومنهجي من خلال إرساء نظام محاسبي متكامل الأركان, والمقومات, وبما يتلاءم مع خصائص النشاط الزراعي والعوامل المؤثرة فيه. وقد تناول البحث المقومات الأساسية لنظام محاسبة التكاليف الزراعية، والمعالجة المحاسبية لكافة عناصر التكاليف الزراعية، والمحاسبة عن بعض الأنشطة الإنتاجية الرئيسية في المنشآت الزراعية كإنتاج المحاصيل وإنتاج الشتلات الزراعية، وإنتاج الفواكه والثمار. كما تناول البحث أيضا الرقابة, وتقويم الأداء في المنشآت الزراعية من خلال التركيز على المقومات الأساسية للرقابة وتقويم الأداء, وهذه المقومات هي: وجود نظام محاسبة تكاليف زراعية- بناء الموازنات التخطيطية- إيجاد نظام لتسعير التحويلات الداخلية. وبناءً على هذه الدراسة, فقد تم تقديم مجموعة من المقترحات, والتوصيات التي تساعد على تطوير النظام المحاسبي القائم, ورفع كفاءته في قياس تكلفة المنتجات الزراعية بشكلٍ سليم, وتقديم البيانات المحاسبية اللازمة للتخطيط, والرقابة واتخاذ القرارات المناسبة. The research deals with the accounting of agricultural activity and the possibility of developing it with an applied study on: Al- hurieh installation of vegetable production in Jebleh through out studying the current situation of the agricultural accounting and revealing its shortages and working to develop it scientifically and methodlogically through establishing and integrated ingredients and elements accounting system which is suitable with the characteristics of agricultural activity and elements affecting it. Also the research deals with the main elements of the agricultural, costs accounting system, the accounting treating of the whole agricultural costs elements, and the accounting of some main productive activity in the agricultural installations such as crops production, agricultural seedlings production and fruits productions. As well as the research deals with the control and performance evaluation in the agricultural installations through out focussing on the main ingredients of control and performance evaluation. These ingredients are as follows: existence of the agricultural costs accounting system, establishing planning budgets, and finding a system for pricing the internal transfers. According to the previous analytical study, a set of proposals and recommediations which aid to develop the existent accounting system and to raise it efficiency in measuring the cost of agricultural productions in a correct ways, and providing the accounting data required for the planning and control and taking the suitable decisions.